Analysis of Handling of Default Cases in Debts and Receivables of the Deputy Regent of Sidoarjo - Veronica, Ester; Ramadhani, Sinta; Tarina, Dwi Desi Yaya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This article discusses the phenomenon of breach of contract in debt collection issues by taking a case study of breach of contract involving the Deputy Regent of Sidoarjo. Through conceptual review and tracing of specific cases, this article explores the legal and social implications of breach of contract in lending relationships. By analyzing legal approaches and related court decisions, the article aims to provide deeper insights into how the law handles contract violations and their consequences, particularly in the realm of governance. The implications of the findings of this article also discuss the need for honesty, responsibility, and fair law enforcement in maintaining public trust in legal institutions.